Blood meal as an amino acid source in swine diets - Allee, G.L.; Koch, B.A.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials involving 94 pigs were conducted to evaluate blood meal as a supplemental amino acid source in swine diets. Performance of growing pigs was markedly reduced when blood meal completely replaced soybean meal as a supplemental amino acid source. Adding 0.1% L-isoleucine to the corn-blood meal diet significantly improved daily gain and feed efficiency. However, growing pigs fed any diet containing blood meal in place of soybean meal had reduced performance. Finishing pigs fed blood meal as a partial or total replacement for soybean meal gained at the same rate and were just as efficient in feed utilization as did those fed the corn-soybean diet. These results suggest that blood meal can be fed as the sole supplemental amino acid source in the diet of finishing pigs but not in the diet of growing pigs.
Swine Industry Day 1974 is known as Swine Day, 1974
Keywords: Swine; Blood meal; Amino acid; Corn-soybean meal